1999
DOI: 10.1093/brain/122.12.2321
|View full text |Cite
|
Sign up to set email alerts
|

Primary CA1 and conditionally immortal MHP36 cell grafts restore conditional discrimination learning and recall in marmosets after excitotoxic lesions of the hippocampal CA1 field

Abstract: Common marmosets (Callithrix jacchus, n = 18) were trained to discriminate between rewarded and non-rewarded objects (simple discriminations, SDs) and to make conditional discriminations (CDs) when presented sequentially with two different pairs of identical objects signifying reward either in the right or left food well of the Wisconsin General Test Apparatus. After bilateral N-methyl-D-aspartate (0.12 M) lesions through the cornu ammonis-1 (CA1) field (7 microl in five sites), marmosets showed profound impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(26 citation statements)
references
References 43 publications
0
24
0
2
Order By: Relevance
“…Cells established from embryonic and early post-natal tissue retain their ability to follow key aspects of the normal differentiation pathway in vitro when the T-antigen is inactivated . Furthermore, cells derived from the embryonic brain of the Immortomouse differentiate structurally and functionally following transplantation in vivo (Virley et al, 1999), suggesting that the T-antigen does not alter them irreversibly.…”
Section: Introductionmentioning
confidence: 99%
“…Cells established from embryonic and early post-natal tissue retain their ability to follow key aspects of the normal differentiation pathway in vitro when the T-antigen is inactivated . Furthermore, cells derived from the embryonic brain of the Immortomouse differentiate structurally and functionally following transplantation in vivo (Virley et al, 1999), suggesting that the T-antigen does not alter them irreversibly.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that transplantation of fetal cells from the hippocampal CA1 field or multipotent stem cells into damaged hippocampal CA1 field in rats and monkeys led to partial recovery of the damaged brain tissue [9,11,15].…”
mentioning
confidence: 99%
“…[48] Experiments using intrahippocampal transplantation of hippocampal cells in primates with neurotoxic lesions of the hippocampus have shown that the hippocampus is required for the formation and recall, but not the storage, of memories. [51] Damage to the hippocampus does not affect some types of memory, such as the ability to learn new skills (playing a musical instrument or solving certain types of puzzles, for example). This fact suggests that such abilities depend on different types of memory (procedural memory) and different brain regions.…”
Section: Role In Memorymentioning
confidence: 99%